Integrons in the development of antimicrobial resistance: critical review and perspectives - Bhat, Basharat Ahmad; Mir, Rakeeb Ahmad; Qadri, Hafsa; Dhiman, Rohan; Almilaibary, Abdullah; Alkhanani, Mustfa; Mir, Manzoor Ahmad (Frontiers in Microbiology, 2023)
Antibiotic resistance development and pathogen cross-dissemination are both considered important risks to human health. Antimicrobial resistance genes (AMRs) are acquired, expressed, disseminated, and traded mostly by integrons, the key players capable of transferring genes from bacterial chromosomes to plasmids and their integration by integrase to the target pathogenic host. Integrons exhibit a large and concealed diversity in the natural environment, which raises concerns about their potential wider application in bacterial adaptation. They should be viewed as a dangerous pool of resistance determinants from the One Health approach. Amongst the 3 documented classes of integrons class I has been found frequently associated with AMRs in humans and is a critical genetic element to serve as a target for therapeutics to AMRs through gene silencing or combinatorial therapies. The direct method of screening gene cassettes linked to pathogenesis and resistance harbored by integrons is a novel way to assess human health. The last decade witnessed surveying the integron-associated gene cassettes associated with the increase in drug tolerance and rising pathogenicity of human pathogenic microbes. Consequently, we aimed to unravel the structure and functions of integrons and their mechanism of integration through understanding horizontal gene transfer from one trophic group to another. Assessment of AMRs and prevailing antibiotic resistance by integrons in humans is grossly detailed. The current studies on integrons will pave the way to clinical understanding for devising a roadmap solution to AMR and pathogenicity.